Temperature Dependence of NMR T1 Relaxation of Dibenzo Diaza 18-Crown-6 Ether Derivative in Solution - ZAFER KOYLU, M.; BUDAK, HATICE (Asian Journal of Chemistry, 2010)
Spin-lattice relaxation times in one of dibenzo diaza 18-crown-6 ether derivative were measured vs. increasing temperature. The relaxation times (ln T1) were fitted vs. l/T over a temperature range of 313-277 K. A linear relationship with a negative slope was found for each peak. The present data suggest that ln T1 is nearly linearly proportional to l/T. The data also suggest that dipole-dipole interaction, modulated by whole molecular tumbling, is the source of relaxation.